Biosynthesis and Cellular Functions of Tartaric Acid in Grapevines - Burbidge, Crista Ann; Ford, Christopher Michael; Melino, Vanessa Jane; Wong, Darren Chern Jan; Jia, Yong; Jenkins, Colin Leslie Dow; Soole, Kathleen Lydia; Castellarin, Simone Diego; Darriet, Philippe; Rienth, Markus; Bonghi, Claudio; Walker, Robert Peter; et al. (Frontiers in Plant Science, 2021)
Tartaric acid (TA) is an obscure end point to the catabolism of ascorbic acid (Asc). Here, it is proposed as a “specialized primary metabolite”, originating from carbohydrate metabolism but with restricted distribution within the plant kingdom and lack of known function in primary metabolic pathways. Grapes fall into the list of high TA-accumulators, with biosynthesis occurring in both leaf and berry. Very little is known of the TA biosynthetic pathway enzymes in any plant species, although recently some progress has been made in this space. New technologies in grapevine research such as the development of global co-expression network analysis tools and genome-wide association studies, should enable more rapid progress. There is also a lack of information regarding roles for this organic acid in plant metabolism. Therefore this review aims to briefly summarize current knowledge about the key intermediates and enzymes of TA biosynthesis in grapes and the regulation of its precursor, ascorbate, followed by speculative discussion around the potential roles of TA based on current knowledge of Asc metabolism, TA biosynthetic enzymes and other aspects of fruit metabolism.